Multi-dimensional approaches to scaling up coral reef restoration. (September 2022) - Lamont, Timothy A.C.; Razak, Tries B.; Djohani, Rili; Janetski, Noel; Rapi, Saipul; Mars, Frank; Smith, David J.
Abstract: Local and global stressors have led to rapid declines in coral reef health around the world. A range of active restoration techniques have recently been introduced in attempts to stem and reverse this decline, but their efficacy is debated. In particular, restoration faces the challenge of scale; successful projects must be deployed quickly over large areas, without being prohibitively expensive. Indonesia has more coral reefs – and more coral reef restoration programmes – than any other country on Earth. The past two decades have seen a rapid expansion in the scale of Indonesia's restoration efforts. Having started in the 1980s, there are now hundreds of individual programmes across the country, several of which have outplanted tens of thousands of corals. Here, we identify ten different social, economic and environmental approaches that have contributed to this scaling up of reef restoration in Indonesia. We discuss the theoretical basis for each approach and provide case studies of their implementation from sixteen different Indonesian programmes. In combination, these diverse approaches have created opportunities to increase the operational efficiency, spatial scale, speed of deployment and social inclusivity of reef restoration in many different contexts. Their examples represent valuable learning experiences, highlighting a range of mechanisms through which management and policy interventions might aim to increase the scale of coral reef restoration. By combining ecological, social and economic strategies in a multi-dimensional approach to scale-up, reef restoration can deliver more beneficial and equitable outcomes locally, regionally and globally.